Surface Contamination of Reusable Respirators and Face Shields During Care of Critically Ill COVID-19 Patients. (March 2023) - Shah, Anand; Zhuang, Eileen; German, Jennifer; Tai, Sheldon; Schanz, Maria; Glendening, Gabrielle; Mason, Mackenzie; Kolesnik, Olga; Hines, Stella E.
Background: With the emergence of SARS-CoV-2, healthcare workers (HCW) have relied on reusable personal protective equipment (PPE), including respirators and face shields (FSs). The effectiveness of decontamination procedures outside experimental settings is unclear. We examined the prevalence of surface contamination on reusable PPE used by HCWs at a hospital incorporating daily centralized decontamination and post-use wiping by sampling for common pathogens. Method: Samples were collected from HCWs' CleanSpace Halo respirator face masks (FMs) and FSs at the start of shift, immediately after use, and after cleaning with disinfecting wipes. Samples were analyzed for pathogens using the Applied Biosystems™ TaqPath™ COVID-19 Combo Kit and ThermoFisher TaqMan Array Card. Patient charts were reviewed for clinical correlation. Findings: Of the 89 samples, 51 from FMs and 38 from FSs, none tested positive for SARS-CoV-2, despite 58 being obtained from PPE used in the care of patients with COVID-19, many with recent aerosol-generating procedures. Four samples tested positive (4.5%) for Staphylococcus aureus, two each from FMs and FSs. FMs that tested positive were not worn concurrently with FSs that tested positive. The FM and FS samples testing positive were worn in the care of patients without diagnosed S. aureus infection. No FMs tested positive following wipe-based disinfection, but both positive FS samples were found after disinfection wiping. Conclusion/Application to Practice: Contamination of reusable PPE appears uncommon, especially with SARS-CoV-2, when regular decontamination programs are in place. The rare presence of S. aureus highlights the importance of doffing procedures and hand hygiene by HCW to prevent surface contamination.